144k views
1 vote
7(3b-1)=2b-26 please help and give me step by step ☺️​

User Topched
by
5.2k points

2 Answers

6 votes

Answer:

b = -1

Explanation:

7(3b -1 ) = 2b - 26

First, distribute.

21b - 7 = 2b - 26

Then, add 7 to both sides AND subtract 2b on both sides

21b - 7 + 7 - 2b = 2b - 2b - 26 + 7

Add common terms

19b = -19

Divide by 19

b = -1

User Khuram
by
5.0k points
1 vote

Answer:

b = -1

Explanation:

7(3b-1): 7 goes into the numbers by multiplying. This will give you 21b-7.

So now the equation should be like 21b-7=2b-26.

-7 and 2b swap places, making 21b-2b=7-26. It will give you 19b= -19.

Finally divide the two numbers (-19 / 19) and the solution will be b= -1.

If I didn't make a clear answer or a good explanation, please comment. I sometimes mess up my steps, and this is my first time using this.

User Theo Yaung
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.